Educational Gender Disparity in Rajastan (An Analytical Study on Women Education) - Gaur, K. D; Sidana, Kusum (Journal of Commerce and Trade, 2008)
This paper attempts to analyze gender disparity in the field of education in Rajasthan. After many years of independence, It is observed that women are still lagging behind to men in sphere of education. The main reason is the social customs and traditions affect the women education in Rajasthan. This study is based on census 2001 and data is analyzed by ranking and coeffieient of variations. This study concluded that variations have been observed in male and female literacy rate in various districts of Rajasthan. It is further observed that along with gender disparity, the regional disparity is also observed in Rajasthan with respect to women education. In terms of education, rural women are far behing to urban women in Rajasthan.